2024
DOI: 10.1021/acs.nanolett.3c04435
|View full text |Cite
|
Sign up to set email alerts
|

Experimental High-Resolution Observation of the Truncated Double-Icosahedron Structure: A Stable Twinned Shell in Alloyed Au–Ag Core@Shell Nanoparticles

Rubén Mendoza-Cruz,
Juan Pedro Palomares-Báez,
Stephan Mario López-López
et al.

Abstract: Given the binary nature of nanoalloy systems, their properties are dependent on their size, shape, structure, composition, and chemical ordering. When energy and entropic factors for shapes and structure variations are considered in nanoparticle growth, the spectra of shapes become so vast that even metastable arrangements have been reported under ambient conditions. Experimental and theoretical variations of multiply twinned particles have been observed, from the Ino and Marks decahedra to polyicosahedra and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 83 publications
(142 reference statements)
3
3
0
Order By: Relevance
“…Collectively, the observed edge contractions, expansion of central plane atoms, and increase in Δc5∠ strongly suggest a tendency of NPs to assume a more rounded configuration as additional layers are added. These findings align with observations from TEM images reported by Shankar et al and aberration-corrected HAADF by Cruz and co-workers …”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Collectively, the observed edge contractions, expansion of central plane atoms, and increase in Δc5∠ strongly suggest a tendency of NPs to assume a more rounded configuration as additional layers are added. These findings align with observations from TEM images reported by Shankar et al and aberration-corrected HAADF by Cruz and co-workers …”
Section: Resultssupporting
confidence: 92%
“…Our findings showed that it is generally easier to add gold layers onto silver cores than the other way around, which was consistent across different NP sizes, aligning with previous experimental data and simulations for AuAg alloy NPs by Andolina et al, Cruz and co-workers, and Gromoff et al, that overall suggested that gold surface segregation can be observed in vacuum while silver surface segregation is usually found in more reactive conditions.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations